A method for recycling lithium battery positive electrode materials with low energy consumption and high efficiency
By using sodium hypophosphite, ammonium formate and tannin as reducing agents in the recovery of lithium battery positive electrode materials, and humic acid-acrylic graft copolymers as dispersants, the problems of high energy consumption and long leaching time in the prior art are solved, and the recovery of lithium battery positive electrode materials with low energy consumption and high efficiency is achieved.
Patent Information
- Application Number
- CN202210483076.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-05-06
AI Technical Summary
The prior art requires higher temperature and high-speed stirring when recycling lithium battery positive electrode materials, resulting in higher energy consumption and longer leaching process time.
Sodium hypophosphate, ammonium formate and tannin are used as reducing agents, combined with humic acid-acrylic graft copolymer as dispersant, and leaching reaction is carried out at room temperature by low-speed stirring, and the pH value is adjusted to improve the leaching efficiency.
It realizes efficient recovery of the lithium battery positive electrode material under normal temperature and low speed stirring, reduces energy consumption, and improves leaching rate and dispersion stability.
Smart Images

Figure DEST_PATH_IMAGE001
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery recycling and provides a method for recycling lithium battery positive electrode materials with low energy consumption and high efficiency. Background Art
[0002] As one of the most popular new energy batteries in the world today, lithium batteries have the advantages of long service life, low self-discharge rate, high energy density, light weight and environmental friendliness. They have been widely used in energy storage systems such as solar energy, water conservancy and thermal power. They are also widely used in electronic products such as mobile phones and computers, as well as electric vehicles.
[0003] Lithium batteries are mainly composed of positive electrodes, negative electrodes, diaphragms, electrolytes (electrolytes), and shells. The main materials are polymers and metal materials. Discarded lithium batteries contain not only toxic and harmful substances such as heavy metals, organic electrolytes (electrolytes), polymers, etc., which pollute the environment and affect human health, but also cause waste of resources. It should be noted that the valuable metals, graphite carbon, and electrolytes (electrolytes) in the electrodes of lithium batteries are all very valuable materials for recycling. Therefore, the recycling of lithium batteries is of great significance to the development of the lithium battery industry.
[0004] At present, the recycling and utilization processes of waste lithium batteries are mainly divided into pyrometallurgy, hydrometallurgy and biological methods. The process of pyrometallurgy is complex, costly, and easily produces substances that pollute the environment. Biometallurgy requires the cultivation of microorganisms that can serve as metal dissolving media, which is difficult to cultivate and the effect is average. Hydrometallurgy mainly includes processes such as leaching, precipitation and extraction. Among them, leaching mainly uses a leaching agent to dissolve the target metal in the positive electrode active material, which is a key step in hydrometallurgy. The leaching agents commonly used in hydrometallurgy are mainly acid solutions, including common organic acids and inorganic acids. A certain amount of reducing agents and dispersants can be added during acid leaching. The reducing agent can increase the leaching rate of the metal, and the dispersant can avoid the aggregation of active materials and improve the leaching effect.
[0005] However, conventional acid leaching to recover positive electrode materials for lithium batteries requires not only high temperatures but also high-speed stirring, resulting in high energy consumption and a long leaching process. Summary of the invention
[0006] In order to reduce the energy consumption of acid leaching to recover metals and improve the leaching efficiency, the present invention proposes a method for recovering lithium battery positive electrode materials with low energy consumption and high efficiency, using sodium hypophosphite, ammonium formate and tannic acid as reducing agents and humic acid-acrylic acid graft copolymer as dispersant, which can achieve low energy consumption and high efficiency in the recovery process.
[0007] To achieve the above purpose, the specific technical solution of the present invention is as follows:
[0008] A method for recycling lithium battery positive electrode materials with low energy consumption and high efficiency, comprising the following steps:
[0009] (1) Discharging the recycled waste lithium batteries and then disassembling them to separate the positive electrode, negative electrode, separator and shell, and then separating the active material of the positive electrode and the current collector to obtain the active material;
[0010] (2) Sodium hypophosphite, ammonium formate and tannic acid are used as reducing agents and added to water together with a dispersant, and the mixture is stirred evenly. The pH value is adjusted to 6, and then the active material obtained in step (1) is added, and the reaction is stirred at a low speed at room temperature to reduce the high-valent metal ions in the active material. Then, acid solution is added to the system, the pH value is adjusted to 2-3, and the leaching is continued at a low speed. The leaching is filtered to obtain a leachate containing recovered metal ions; the dispersant is a humic acid-acrylic acid graft copolymer.
[0011] Before recycling used lithium batteries, it is necessary to ensure that the residual power is fully consumed to prevent the risk of explosion caused by local overheating due to the rapid release of residual power caused by battery short circuit during disassembly. Traditional discharge methods mainly include physical discharge and chemical discharge. Preferably, the discharge process in step (1) is to place the used lithium battery in a sodium chloride solution with a mass concentration of 2-4%, discharge for 3-5 hours, and air-dry for standby use.
[0012] After the waste lithium battery is fully discharged, it is manually or mechanically disassembled and separated into components such as the positive electrode, negative electrode, diaphragm and shell. The positive electrode is generally bonded to the aluminum foil with a binder. Therefore, the positive electrode active material must be separated from the current collector and the binder must be removed. Preferably, the process of separating the active material and the current collector of the positive electrode in step (1) is divided into two steps: a. First, the positive electrode is added to a sodium hydroxide solution with a mass concentration of 4-5% and stirred for 20-30 minutes to make the aluminum foil fall off and separate, and the filtrate is filtered and washed until the filtrate is neutral, and the filter residue is dried; b. The dried filter residue is added to an organic solvent, ultrasonically treated for 5-8 hours to remove the binder, followed by centrifugal separation, washing with anhydrous ethanol, and drying to obtain the active material. Further preferably, the organic solvent is at least one of N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and dimethyl sulfoxide.
[0013] In the leaching process of the present invention, acid solution is used as a leaching agent to leach metals such as cobalt, manganese, nickel, iron, and lithium in the positive electrode material. Since the chemical bonds between the atoms of each valuable metal in the active material are extremely strong, and the valence states of cobalt, nickel, and manganese are relatively high, if complete leaching is desired, a certain amount of reducing agent needs to be added to form an oxidation-reduction reaction, thereby increasing the leaching rate. Preferably, the acid solution in step (2) is a hydrochloric acid solution with a mass concentration of 37%.
[0014] The present invention uses sodium hypophosphite, ammonium formate and tannic acid as reducing agents, and can realize a reduction reaction at room temperature. It not only has low energy consumption, but also has a simple reaction process and is suitable for large-scale application. In the specific operation, the reducing agent and dispersant are first added to the water and stirred evenly, and the pH value of the system is adjusted to 6. The weak acid environment is conducive to the reduction reaction. Preferably, the amount of sodium hypophosphite added in step (2) is 2-3% of the water mass, the amount of ammonium formate added is 3-5% of the water mass, and the amount of tannic acid added is 2-3% of the water mass. Further preferably, the amount of active material added in step (2) is 3-6% of the water mass.
[0015] Since the active material is easy to aggregate, especially as the reduction and leaching are carried out, the particle size of the active material is continuously reduced and the tendency to agglomerate increases, so it is necessary to add a dispersant. Although tannic acid itself has a certain dispersing effect, the dispersion stability is poor and high-speed stirring is required to ensure effective dispersion. Currently commonly used dispersants (such as polyvinyl pyrrolidone) also need to be stirred at a high speed to achieve a high leaching rate. The present invention uses humic acid-acrylic acid graft copolymer as a dispersant, which significantly improves the dispersion stability, allows the reduction and leaching process to be carried out under low-speed stirring, and solves the problem that the reduction leaching in the prior art requires high-speed stirring and high energy consumption. Preferably, the amount of the dispersant added is 0.03-0.05% of the water mass. Preferably, the stirring speed of the low-speed stirring reaction in step (2) is 30-60rpm, and the time is 30-50min; the stirring speed of the low-speed stirring leaching in step (2) is 30-60rpm, and the time is 10-20min. The humic acid-acrylic acid graft copolymer can be prepared according to the prior art.
[0016] The present invention provides a method for recovering positive electrode materials of lithium batteries with low energy consumption and high efficiency. Compared with the prior art, the outstanding features and excellent effects of the present invention are as follows: on the one hand, the present invention uses sodium hypophosphite, ammonium formate and tannic acid as reducing agents, which can reduce and leach metals in positive electrode materials of lithium batteries at room temperature, and the leaching rate is relatively high. On the other hand, the present invention uses humic acid-acrylic acid graft copolymer as a dispersant, which improves the dispersion stability and enables the reduction and leaching processes to be carried out under low-speed stirring. It can be seen that the recovery process of the present invention has low energy consumption and high efficiency, and is convenient for large-scale promotion and application. DETAILED DESCRIPTION
[0017] Example 1
[0018] (1) Discharging the recycled waste lithium cobalt oxide battery, and then disassembling it to separate the positive electrode, negative electrode, separator and shell, and then separating the active material of the positive electrode from the current collector to obtain the active material; the discharge process is to place the waste lithium battery in a sodium chloride solution with a mass concentration of 2%, discharge for 5 hours, and air-dry for standby use; the process of separating the active material of the positive electrode from the current collector is divided into two steps, a, first adding the positive electrode to a sodium hydroxide solution with a mass concentration of 4% and stirring for 30 minutes to make the aluminum foil fall off and separate, filtering and washing until the filtrate is neutral, and drying the filter residue; b, adding the dried filter residue to N-methylpyrrolidone, ultrasonically treating it for 5 hours to remove the binder, and then centrifuging, washing with anhydrous ethanol, and drying to obtain the active material;
[0019] (2) Sodium hypophosphite, ammonium formate and tannic acid are added to water as reducing agents together with a dispersant, mixed and stirred evenly, the pH value is adjusted to 6, and then the active material obtained in step (1) is added, and the reaction is stirred at a low speed at room temperature to reduce the high-valent metal ions in the active material. Then, an acid solution is added to the system, the pH value is adjusted to 2, and the leaching is continued at a low speed. After filtering, a leachate containing recovered metal ions is obtained; the dispersant is a humic acid-acrylic acid graft copolymer, and the amount of the dispersant added is 0.03% of the water mass; the amount of the active material added is 6% of the water mass; the amount of sodium hypophosphite added is 2% of the water mass, the amount of ammonium formate added is 3% of the water mass, and the amount of tannic acid added is 2% of the water mass; the stirring speed of the low-speed stirring reaction is 30 rpm, and the time is 40 min; the acid solution is a hydrochloric acid solution with a mass concentration of 37%; the stirring speed of the low-speed stirring leaching is 30 rpm, and the time is 15 min.
[0020] Example 2
[0021] (1) Discharging the recycled waste lithium manganese oxide battery and then disassembling it to separate the positive electrode, negative electrode, separator and shell, and then separating the active material of the positive electrode from the current collector to obtain the active material; the discharge process is to place the waste lithium battery in a sodium chloride solution with a mass concentration of 3%, discharge for 4 hours, and air-dry for standby use; the process of separating the active material of the positive electrode from the current collector is divided into two steps, a, first adding the positive electrode to a sodium hydroxide solution with a mass concentration of 4.5% and stirring for 25 minutes to make the aluminum foil fall off and separate, filtering and washing until the filtrate is neutral, and drying the filter residue; b, adding the dried filter residue to dimethylacetamide, ultrasonically treating for 6.5 hours to remove the binder, and then centrifuging, washing with anhydrous ethanol, and drying to obtain the active material;
[0022] (2) Sodium hypophosphite, ammonium formate and tannic acid are added to water as reducing agents together with a dispersant, mixed and stirred evenly, the pH value is adjusted to 6, and then the active material obtained in step (1) is added, and the reaction is stirred at a low speed at room temperature to reduce the high-valent metal ions in the active material. Then, an acid solution is added to the system, the pH value is adjusted to 2.5, and the leaching is continued at a low speed. After filtering, a leachate containing recovered metal ions is obtained; the dispersant is a humic acid-acrylic acid graft copolymer, and the amount of the dispersant added is 0.04% of the water mass; the amount of the active material added is 4.5% of the water mass; the amount of sodium hypophosphite added is 2.5% of the water mass, the amount of ammonium formate added is 4% of the water mass, and the amount of tannic acid added is 2.5% of the water mass; the stirring speed of the low-speed stirring reaction is 45 rpm, and the time is 40 min; the acid solution is a hydrochloric acid solution with a mass concentration of 37%; the stirring speed of the low-speed stirring leaching is 45 rpm, and the time is 15 min.
[0023] Example 3
[0024] (1) Discharging the recycled waste nickel cobalt manganese oxide batteries, and then disassembling them to separate the positive electrode, negative electrode, separator and shell, and then separating the active material of the positive electrode from the current collector to obtain the active material; the discharge process is to place the waste lithium battery in a sodium chloride solution with a mass concentration of 4%, discharge for 3 hours, and air-dry for standby use; the process of separating the active material of the positive electrode from the current collector is divided into two steps, a, first adding the positive electrode to a sodium hydroxide solution with a mass concentration of 5% and stirring for 20 minutes to make the aluminum foil fall off and separate, filtering and washing until the filtrate is neutral, and drying the filter residue; b, adding the dried filter residue to dimethylformamide, ultrasonically treating for 8 hours to remove the binder, and then centrifuging, washing with anhydrous ethanol, and drying to obtain the active material;
[0025] (2) Sodium hypophosphite, ammonium formate and tannic acid are added to water as reducing agents together with a dispersant, mixed and stirred evenly, the pH value is adjusted to 6, and then the active material obtained in step (1) is added, and the reaction is stirred at a low speed at room temperature to reduce the high-valent metal ions in the active material. Then, an acid solution is added to the system, the pH value is adjusted to 3, and the leaching is continued at a low speed. After filtering, a leachate containing recovered metal ions is obtained; the dispersant is a humic acid-acrylic acid graft copolymer, and the amount of the dispersant added is 0.05% of the water mass; the amount of the active material added is 3% of the water mass; the amount of sodium hypophosphite added is 3% of the water mass, the amount of ammonium formate added is 5% of the water mass, and the amount of tannic acid added is 3% of the water mass; the stirring speed of the low-speed stirring reaction is 60 rpm, and the time is 40 min; the acid solution is a hydrochloric acid solution with a mass concentration of 37%; the stirring speed of the low-speed stirring leaching is 60 rpm, and the time is 15 min.
[0026] Comparative Example 1
[0027] In Comparative Example 1, polyvinyl pyrrolidone is used as the dispersant, and the other components are the same as those in Example 1.
[0028] Comparative Example 2
[0029] Comparative Example 2 uses polyvinyl pyrrolidone as the dispersant, and the rest is the same as that of Example 2.
[0030] Comparative Example 3
[0031] Comparative Example 3 uses polyvinyl pyrrolidone as the dispersant, and the rest is consistent with Example 3.
[0032] The humic acid-acrylic acid graft copolymer used above is prepared by the existing technology: humic acid is added to distilled water, the pH value is adjusted to 9 with a dilute sodium hydroxide solution, the temperature is raised to 70°C under nitrogen protection, and the solution is stirred to be fully dissolved; then a potassium persulfate initiator solution and an acrylic acid solution are slowly added dropwise, and the addition is completed within 1 hour, followed by heat preservation and reaction for 2 hours; cooled to room temperature, the pH value is adjusted to neutral with dilute hydrochloric acid, and filtered to obtain a humic acid-acrylic acid graft copolymer; the amount of acrylic acid monomer used is 35% of the mass of the humic acid; the amount of initiator used is 4% of the total mass of the humic acid and acrylic acid monomers.
[0033] Performance test: Collect the leachate and filter residue of Examples 1-3 and Comparative Examples 1-3, dry the filter residue, cool it to room temperature, digest it with aqua regia, filter it, and obtain the filter residue digestion solution. Then use ICP-AES (inductively coupled plasma spectrometer) to perform ion analysis on the leachate and filter residue digestion solution to determine the concentration of various recovered metals; then use the formula to calculate the leaching rate of various recovered metals: Q=C1V1 / (C1V1+C2V2), where Q is the leaching rate of each recovered metal, C1 is the concentration of each recovered metal in the leachate, V1 is the volume of the leachate, C2 is the concentration of each recovered metal in the filter residue digestion solution, and V2 is the volume of the filter residue digestion solution. The calculation results are shown in Table 1.
[0034] Table 1:
[0035]
Claims
1. A method for recovering positive electrode materials of lithium batteries with low energy consumption and high efficiency, characterized in that: The following steps are involved: (1) Discharging the recycled waste lithium batteries and then disassembling them to separate the positive electrode, negative electrode, separator and shell, and then separating the active material of the positive electrode and the current collector to obtain the active material; (2) Sodium hypophosphite, ammonium formate and tannic acid are used as reducing agents and added to water together with a dispersant, and the mixture is stirred evenly. The pH value is adjusted to 6, and then the active material obtained in step (1) is added, and the mixture is stirred at a low speed at room temperature to react to reduce the high-valent metal ions in the active material. Then, an acid solution is added to the system, and the pH value is adjusted to 2-3. The mixture is stirred at a low speed for leaching, and filtered to obtain a leachate containing recovered metal ions; the dispersant is a humic acid-acrylic acid graft copolymer; In step (2), the stirring speed of the low-speed stirring reaction is 30-60 rpm, and the time is 30-50 min; the stirring speed of the low-speed stirring leaching is 30-60 rpm, and the time is 10-20 min.
2. According to claim 1, a method for recovering lithium battery positive electrode materials with low energy consumption and high efficiency, characterized in that: The discharge process in step (1) is to place the waste lithium battery in a sodium chloride solution with a mass concentration of 2-4%, discharge for 3-5 hours, and air-dry for standby use.
3. According to claim 1, a method for recovering lithium battery positive electrode materials with low energy consumption and high efficiency, characterized in that: The process of separating the active material of the positive electrode and the current collector in step (1) is divided into two steps: a. first, adding the positive electrode to a sodium hydroxide solution with a mass concentration of 4-5% and stirring for 20-30 minutes to make the aluminum foil fall off and separate, filtering and washing until the filtrate is neutral, and drying the filter residue; b. adding the dried filter residue to an organic solvent, ultrasonically treating for 5-8 hours to remove the binder, and then centrifugally separating, washing with anhydrous ethanol, and drying to obtain the active material; the organic solvent is at least one of N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and dimethyl sulfoxide.
4. A method for recovering positive electrode materials of lithium batteries with low energy consumption and high efficiency according to claim 1, characterized in that: In step (2), the amount of sodium hypophosphite added is 2-3% of the water mass, the amount of ammonium formate added is 3-5% of the water mass, the amount of tannic acid added is 2-3% of the water mass, the amount of dispersant added is 0.03-0.05% of the water mass, and the amount of active material added is 3-6% of the water mass.
5. A method for recovering lithium battery positive electrode materials with low energy consumption and high efficiency according to claim 1, characterized in that: The acid solution in step (2) is a hydrochloric acid solution with a mass concentration of 37%.
Citation Information
Patent Citations
Method for extracting sulfide minerals of nonferrous metals and method for recycling sulfur in extracted filtered residues thereof
CN101698904A
Method for recovering lithium
CN104105803A